A proportion-integral-derivative closed-loop frequency-locking method for improving the accuracy and sensitivity of a magnetometer. (26th August 2020) - Deng, Shengli; Zhang, Weidong; Guo, Hao; Wu, Dajin; Li, Zhonghao; Wen, Huanfei; Tang, Jun; Han, Xingcheng; Ma, Zongmin; Liu, Jun; Li, Yanjun
Abstract: Proportion-integral-derivative (PID) closed-loop frequency-locking (CLFL) technology has been demonstrated to improve the magnetic field sensitivity of spin-based sensors based on the nitrogen-vacancy (NV) color centers in diamond. First, we analyse the undulation effect of the fluorescence quantum yield of NV centers with a magnetic field. The valley value of the magnetic resonance spectrum have been differential into a zero to insensitive to intensity fluctuations of fluorescence quantum yield of NV centers based on the PID-CLFL technology. Then, the sensitivity of the magnetic field improved from 40 nT Hz −1/2 to 10 nT Hz −1/2 . It proves an effective method to improve the sensitivity of the spin-based sensors.